VALIDITAS KELENGKUNGAN VERTEBRA HASIL FOTO POLOS PROYEKSI LATERAL PADA SPASME MUSKULUS PARASPINAL - , Endrawati Tri Bowo, Prof. dr. Arif Faisal, Sp.Rad(K), DHSM ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Paraspinal muscle spasm is an occurence of muscles sprain around vertebra could be demonstrated cleared with electromyography. The indirect sign is hypolordotic or straight curvature in cervical or lumbal vertebra on plain film lateral projection. The aims of this study were to determine the value of sensitivity, specificity and accuracy of the curvature on plain film lateral projection in diagnosing paraspinal muscle spasm. The study was observational, cross sectional, to develop diagnostic test, 50 patients suffered neck or low back pain having both indicated for cervical or lumbal/lumbosacral lateral projection radiography and electromyography at 1 October 2010 until 31 December 2010, depend on the inclusion and exclusion criterions. Basic characteristic data analyzed by descriptive, validity data were analyzed based on 2x2 tables. The results of this study showed that sensitivity, specificity, positive predictive value, negative predictive value, accuration, and prevalence of plain film lateral projection in determining paraspinal muscle spasm were 90,47%, 86,21%, 82,61%, 92,59%, 88%, and 42 % respectively. Sensitivity and specificity are very depended on the disease prevalence, so that the predictive value from a diagnostic test should be considered in patient management. The high sensitivity and specificity of plain film lateral projection has proven valuable as parameter in paraspinal muscle spasm either for screening or diagnostic purpose. Hypolordotic or straight curvature in cervical or lumbal vertebra on plain film lateral projection could be used as basic for radiological diagnosis, because it is simply, easy, comfort, and cheap in paraspinal muscle spasm.